Latissimus Dorsi Transfer for Triceps Brachii Reconstruction in a Patient with Leiomyosarcoma of the Triceps Brachii: Technique and Case Report - Rezende, Luis Guilherme Rosifini Alves; Shimaoka, Filipe Jun; Mandarano-Filho, Luiz Garcia; Gava, Nelson Fabrício; Engel, Edgard Eduard; Mazzer, Nilton (ARCHIVES OF HEALTH INVESTIGATION, 2022)
Reconstruction surgeries for malignant soft tissue tumors challenges many surgeons and orthopedic centers. Few cases of triceps brachii leiomyosarcoma reconstruction have been described. There are tunneling techniques already described by other authors. This study aims to report a case of oncological reconstruction of the triceps brachii using the large Latissimus Dorsi flap in a 60 years-old male patient with leiomyosarcoma in the triceps brachii. The patient achieved full recovery of triceps brachii function after eight weeks. The microsurgical options could be helpful in the management and reconstruction of the leiomyosarcomas in patients without limb amputation indication.